NON-TRADITIONAL RISK FACTOR ASSOCIATED WITH ACUTE CORONARY SYNDROME IN YOUNG AGE : A SYSTEMATIC REVIEW - Derrick; Halim, Hendry (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
In younger people all across the world, acute coronary syndrome remains one of the primary causes of death and disability. This is especially true in developing countries. Due to the fact that little reporting has taken place, there is a severe lack of data relevant to the patient group in question. Traditional risk factors, which are risk factors that have been well documented to increase the likelihood of developing acute coronary syndrome, such as smoking, hyperlipidemia, hypertension, a family history of atherosclerosis, a family history of obesity, and diabetes mellitus (DM), are becoming more prevalent in the younger population. In addition, illnesses that are typically uncommon among adults, including as obstructive sleep apnea (OSA), rheumatoid arthritis (RA), and systemic lupus erythematosus (SLE), are more prevalent in younger patients with AMI. [Citation needed] Studies highlight the significant frequency and importance of established atherosclerotic risk factors such as smoking, hypertension, and a family history of coronary artery disease in addition to emerging risk factors such as systemic lupus erythematosus, obstructive sleep apnea, and HIV. These risk factors include smoking, hypertension, and a family history of coronary artery disease. In spite of the fact that we emphasize the significance of the non-traditional risk factors that were described earlier, it is essential to identify young patients who have traditional risk factors, and in particular those who have coexisting diseases such as HIV, OSA, and SLE, and to optimize their treatment in a way that takes these factors into account. In addition, we highlight the significance of the non-traditional risk factors that were described earlier.